Public Intimacies: Frances Burney’s and Jane Cave Winscom’s Accounts of Illness - Béres Rogers, Kathleen (Romanticism and Victorianism on the Net, 2012)
This article argues that, in a culture that focused on either essentializing or universalizing women’s bodies, Frances Burney’s 1811 Mastectomy Letter and Jane Cave Winscom’s 1793 Headache Odes utilize physiologically specific language to challenge these dominant ideals. By giving their readers graphic accounts of their procedures and pain, these authors bring their specific bodily experiences to light. Circulating their accounts, respectively as letters and in a local newspaper, Burney and Winscom also negotiate between the intimate sphere of their bodies and the more public space of letters and print.